Introduction: Queer Methods - Brim, Matt; Ghaziani, Amin (Women's studies quarterly, 2016)
To take her example, ACT UP was grounded in goal-oriented tactics and techniques including direct actions (e.g., teach-ins, kiss-ins, and die-ins), building coalitions across race and gender (e.g., affinity groups), highly stylized graphic designs, medical interventions (e.g., needle exchange, inclusive clinical trials, lay expertise4), video/media innovation, acts of disclosing, self-nominating, public shaming, outing, and marching. [...]Hannah McCann focuses on strategies for locating the subject.